Developing Oral Language Using Illustrated Books - Christie, Nancy B. (Qualitative and Quantitative Methods in Libraries, 2019)
The purpose of this study was to complete a content analysis to discern the number of oral language characteristics present in illustrated books in the Emanuel Benjamin Oliver Elementary School Library Easy collection. A content analysis of a sample of 768 books determined the presence of two or more oral language characteristics: no words, repetitive words, rhyming words, song lyrics, and humorous words and/or pictures. The results suggest the selection process for the acquisition of books meant for the development of oral language in Easy collections should be made by examining the content of the books to determine the number of oral language characteristics in the selected books.